2020
DOI: 10.1080/20008198.2020.1764722
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder in volunteer firefighters: influence of specific risk and protective factors

Abstract: Background: Volunteer firefighters belong to a risk population regarding the development of posttraumatic stress disorder (PTSD). However, given the frequency of work-related trauma, PTSD prevalences seem relatively low. Protective factors appear to be effective and are the focus of this study. Objective: We investigated the PTSD-prevalence as well as the influence of trauma exposure and the impact of protective factors resilience and Sense of Coherence (SoC) on symptoms of PTSD in volunteer firefighters. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(75 reference statements)
1
11
0
1
Order By: Relevance
“…In the present study, we found that sense of coherence mediated the association between the severity of PTSD symptoms and resilience, an effect that was also reported by Streb et al ( 16 ) in German paramedic personnel. Moreover, Schnell also identified sense of coherence as a valid predictor of the severity of PTSD symptoms in voluntary firefighters ( 17 ). These findings indicate that sense of coherence might be a valuable target for improving resilience as well as for protecting against PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that sense of coherence mediated the association between the severity of PTSD symptoms and resilience, an effect that was also reported by Streb et al ( 16 ) in German paramedic personnel. Moreover, Schnell also identified sense of coherence as a valid predictor of the severity of PTSD symptoms in voluntary firefighters ( 17 ). These findings indicate that sense of coherence might be a valuable target for improving resilience as well as for protecting against PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To date, almost all studies exploring PTSD symptoms or health-promoting factors in this group have focused on professional rescue personnel, while data on voluntary rescue and emergency personnel are sparse ( 17 ). A recent study found that seasonal firefighters had a higher risk of developing PTSD than did professional firefighters ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In firefighters, reported rates of PTSD vary considerably across studies, ranging from 11% to 37% (Petrie et al, 2018 ). This variability could be related to several factors including – but not limited to – age, sex, training, mentorship system, previous traumatization, and the number of duty-related traumatic incidents (Armour, Fried, Deserno, Tsai, & Pietrzak, 2017 ; Schnell, Suhr, & Weierstall-Pust, 2020 ). Another emerging – yet scarcely studied – factor is the impact of trauma on social interactions (Pfaltz et al, 2019 ) and specifically on interpersonal distance regulation (IDR), which may facilitate the development of PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may emerge because only individuals with high trait resilience choose this profession or due to specific characteristics of occupational trauma (e.g., psychological preparedness). However, although the majority of firefighters may be resilient, some do experience symptoms, warranting further research into the pathogenic processes underlying mental health problems following occupational trauma (Schnell et al, 2020). With respect to PTSD, current research points towards a critical role of endocrinological stress responses during and after trauma (van Zuiden et al, 2019).…”
mentioning
confidence: 99%
“…Despite these detrimental effects of occupational trauma, firefighters experience fewer posttrauma symptoms on average than individuals from the general population involved in the same incidents (Gulliver et al, 2021;Schnell et al, 2020). These effects may emerge because only individuals with high trait resilience choose this profession or due to specific characteristics of occupational trauma (e.g., psychological preparedness).…”
mentioning
confidence: 99%